Pengaruh Vitamin B Pada Pasien Neuropati Diabetik - Syahrizal Syahrizal; Aulia Rahma Asril; Cut Putri Keumala (Jurnal Rumpun Ilmu Kesehatan, 2023)
Diabetes mellitus is a chronic metabolic disease that causes hyperglycemia. Diabetic neuropathy is a complication of diabetes mellitus due to hyperglycemia. People who experience diabetic neuropathy complain of tingling, numbness, stabbing pain sensations, burning pain sensations, squeezing sensations, and allodynia, which can reduce their quality of life. Administering vitamin B reduces patient symptoms and improves nerve cell function. The aim of this study was to explain the effect of vitamin B on patients with diabetic neuropathy based on a literature review. The research method used was literature review. The results of this study, based on some of the reviewed literature, found that vitamin B has an effect on reducing pain complaints in neuropathic patients with diabetes mellitus.